Evaluation of apical extrusion of debris and irrigant using two new reciprocating and one continuous rotation single file systems. - Gurudutt Nayak; Inderpreet Singh; Shashit Shetty; Surya Dahiya (Tehran University of Medical Sciences, 2014)
Apical extrusion of debris and irrigants during cleaning and shaping of the root canal is one of the main causes of periapical inflammation and postoperative flare-ups. The purpose of this study was to quantitatively measure the amount of debris and irrigants extruded apically in single rooted canals using two reciprocating and one rotary single file nickel-titanium instrumentation systems.Sixty human mandibular premolars, randomly assigned to three groups (n = 20) were instrumented using two reciprocating (Reciproc and Wave One) and one rotary (One Shape) single-file nickel-titanium systems. Bidistilled water was used as irrigant with traditional needle irrigation delivery system. Eppendorf tubes were used as test apparatus for collection of debris and irrigant. The volume of extruded irrigant was collected and quantified via 0.1-mL increment measure supplied on the disposable plastic insulin syringe. The liquid inside the tubes was dried and the mean weight of debris was assessed using an electronic microbalance. The data were statistically analysed using Kruskal-Wallis nonparametric test and Mann Whitney U test with Bonferroni adjustment. P-values less than 0.05 were considered significant.The Reciproc file system produced significantly more debris compared with OneShape file system (P0.05). Extrusion of irrigant was statistically insignificant irrespective of the instrument or instrumentation technique used (P >0.05).Although all systems caused apical extrusion of debris and irrigant, continuous rotary instrumentation was associated with less extrusion as compared with the use of reciprocating file systems.